METHOD VALIDATION FOR COPPER DETERMINATION IN HUMAN HAIR SAMPLES THROUGH GRAPHITE FURNACE ATOMIC ABSORPTION SPECTROMETRY - MATEI, Nicoleta; BIRGHILA, Semaghiul; DOBRINAS, Simona; SOCEANU, Alina; ILIE, Ana-Maria; POPESCU, Viorica (Studia Universitatis Babeș-Bolyai Chemia, 2025)
A simple, cheap, and sensitive analytical method was validated for the determination of copper in human hair after microwave digestion. Method validation parameters such as linearity, precision, accuracy, limit of detection (LOD) and limit of quantification (LOQ) were determined. A graphite furnace atomic absorption spectrophotometer has been used. The developed method was linear in the concentration range of 2 - 20 μg/L with a 0.9979 coefficient of determination. The recoveries obtained for the copper ranged from 90.46-94.96%, with a precision not exceeding 3.95% relative standard deviation (RDS%) and system suitability test with RSD% lower than 1.58%. LOD was found to be 0.05632 μg/g and LOQ 0.18745 μg/g. The analyzed samples were from healthy humans and the study shown similar concentration of copper in hairs collected from adult, teenager men and female. The proposed method was considered adequate for the determination of copper in hair samples.